Characterization and Estimation of Genetic Diversity in Two Syrian Chicken Phenotypes Using Molecular Markers - Al-Jallad, Tamara; Choumane , Wafaa; Hmeshe, Mohsen (International Journal of Poultry Science, 2011)
In order to establish pure Syrian local breeds, two chicken phenotypes were collected from the coastal area in Syria. 17 individuals (3 males and 14 females) from each phenotype were analyzed using molecular markers. 11 Operon primers and 10 SSR Primer pairs were used to characterize the chicken genotypes and to estimate their genetic diversity. The level of genetic diversity detected in the black phenotype using the two kinds of markers (0.24533) was higher than that detected in the grey phenotype (0.20453). Dendrogram based on the RAPD and SSR data showed a clear separation between individuals belonging to each phenotype. Based on the obtained results, genotypes with small genetic distance from each phenotype can be selected as parents for the establishment of pure breeds.